2019
DOI: 10.1002/maco.201810618
|View full text |Cite
|
Sign up to set email alerts
|

Field exposure of FeCrAl model alloys in a waste‐fired boiler at 600°C: The influence of Cr and Si on the corrosion behaviour

Abstract: The aim of this study was to examine the performance of FeCrAl model alloys in a waste‐fired boiler and investigate the influence of chromium and silicon content on the corrosion behaviour. The investigation was executed by utilising an air‐cooled probe, giving a material temperature of 600°C throughout a 672 hr exposure. The material loss measurements were performed by utilizing an ultrasonic thickness gauge in combination with scanning electron microscopy analysis. It was found that increasing the chromium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 31 publications
3
10
0
Order By: Relevance
“…7-8 and 10-11), while no grain boundary attack was detected for the alloys with lower Cr content. A similar phenomenon was observed in another study in which FeCrAlSi model alloys were exposed in a waste-fired boiler [15]. It was shown that the general corrosion behavior improved with higher Cr content (reduced material loss) but that the acceleration of the corrosion attack was more prominent on the windward side (in the direction of the flue gas) for alloys with higher Cr-content.…”
Section: Propagationsupporting
confidence: 83%
See 1 more Smart Citation
“…7-8 and 10-11), while no grain boundary attack was detected for the alloys with lower Cr content. A similar phenomenon was observed in another study in which FeCrAlSi model alloys were exposed in a waste-fired boiler [15]. It was shown that the general corrosion behavior improved with higher Cr content (reduced material loss) but that the acceleration of the corrosion attack was more prominent on the windward side (in the direction of the flue gas) for alloys with higher Cr-content.…”
Section: Propagationsupporting
confidence: 83%
“…It was shown that Si significantly improves the secondary protection, by reducing the growth rate of the Fe-rich oxide scale. The same trend was observed when exposing similar alloys in a waste-fired boiler [15]. In addition, Persdotter et al demonstrated the possibility of improving the secondary protection by increasing the amounts of Cr and Al and indications of synergistic interactions between these [11].…”
Section: Introductionsupporting
confidence: 54%
“…In the presence of K 2 CO 3 , Fe10CrAl exhibited a high mass gain (18.4 mg/cm 2 ) which corresponds to a theoretical oxide thickness of 128 µm (based on the assumptions that the mass gain originates from the density change due to the ingress of oxygen and that only magnetite forms [50]). Meanwhile, both Fe15CrAlSi and Fe20CrAlSi exhibited very low mass gain (0.13 and 0.03 mg/cm 2 respectively) which corresponds to oxide thicknesses in the nanometer range, indicating that these alloys have resisted breakaway oxidation.…”
Section: Thermogravimetrymentioning
confidence: 99%
“…Due to their favorable performance properties at high temperatures, Fe-Cr-Al alloys (sometimes referred to as 'fechrals') are actively used as heat-resistant materials that ensure the stable operation of parts under high temperatures (up to 900-1100 • C) and corrosive environments (water vapor, exhaust gases, etc.) typical in the operation of internal combustion engines and power plants, especially when using biofuels [1][2][3][4][5]. According to the study conducted by Zhang et al [1], such a coating successfully withstood heating to a temperature of 900 • C in air for 4 h. As a result, the microstructure of the composite coating became three-layered.…”
Section: Introductionmentioning
confidence: 99%